2014
DOI: 10.1167/iovs.14-15051
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Aqueous Levels of Inflammatory Mediators Between Toxic Anterior Segment Syndrome and Endotoxin-Induced Uveitis Animal Models

Abstract: Prostaglandin E2 and TNF-α in aqueous humor seem to be regulated differently in animal models of TASS and EIU. However, dexamethasone pretreatment improved the clinical findings and inhibited the increases in PGE2 and TNF-α in both animal models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Consistently, the formation of keratic precipitates in the corneal endothelium is characteristic of uveitis [16]. Anterior uveitis involves infiltration of polymorphonuclear inflammatory cells, increased protein permeability, and upregulation of inflammatory cytokines in the aqueous humor [55,56]. In the present study, disrupted endothelial tight junction ZO-1, infiltrated inflammatory cells, and edema of the cornea were significantly induced by LPS treatment; however, these effects were suppressed by fucoxanthin treatment.…”
Section: Discussionsupporting
confidence: 76%
“…Consistently, the formation of keratic precipitates in the corneal endothelium is characteristic of uveitis [16]. Anterior uveitis involves infiltration of polymorphonuclear inflammatory cells, increased protein permeability, and upregulation of inflammatory cytokines in the aqueous humor [55,56]. In the present study, disrupted endothelial tight junction ZO-1, infiltrated inflammatory cells, and edema of the cornea were significantly induced by LPS treatment; however, these effects were suppressed by fucoxanthin treatment.…”
Section: Discussionsupporting
confidence: 76%
“…It has been demonstrated that suppression of inflammation by steroids is related to their inhibitory effects on the production of inflammatory factors such as IL-6 and TNF-α. Therefore, the levels of IL-6 and TNF-α in the inflammatory model were measured after treatment of the cells with different formulations; the results are shown in Figures c,d, respectively. Compared to the levels of IL-6 and TNF-α in cells that received no Dexp treatment (the LPS and HmA groups), the IL-6 and TNF-α levels in cells treated with Dexp (the free Dexp and Dexp@HmA groups) were markedly lower, indicating that Dexp has an ideal anti-inflammatory effect.…”
Section: Resultsmentioning
confidence: 99%
“…In line with this result in FP knock-out mice is the common knowledge that clinical use of cyclo-oxygenase inhibitors does not result in any meaningful change in intraocular pressure. This is despite the fact that all prostanoids are found endogenously present in the eye (27)(28)(29). It seems that under most circumstances prostanoids tending to either increase or decrease intraocular pressure are held in balance and that this balance is not altered, but rather nullified, by global inhibition of prostanoid biosynthesis.…”
Section: Pg 10mentioning
confidence: 99%